Making cassava a truly industrial crop in Nigeria - Musonda, Lucky; Abila, Nelson (Technical Centre for Agricultural and Rural Cooperation, 2018)
A number of national interventions have encouraged the industrialisation of cassava in Nigeria. However, for this industrial revolution to thrive, the value chain needs to become more structured and standardised. To achieve this goal, the Agribusiness Suppliers Development Programme is providing a wide range of support to value chain stakeholders and linking farmers with lead firms.